The Utility of Capsule Endoscopy in Patients under 50 Years of Age with Recurrent Iron Deficiency Anaemia: Is the Juice Worth the Squeeze?. (1st April 2015) - Sidhu, Prabhjot Singh; McAlindon, Mark E.; Drew, Kaye; Sidhu, Reena
Abstract : Background and Aims . The role of capsule endoscopy (CE) in the <50 years of age patients with iron deficiency anaemia (IDA) remains unclear. We aim to assess its utility in this cohort. Methods . All patients referred for CE for recurrent IDA were included retrospectively. Patients were divided into Group 1 (<50 years) and Group 2 (≥50 years). Results . There were 971 patients with recurrent IDA and 28% belonged to Group 1. The mean age was 40 years in this group with a DY of 28% (n = 76 ). Significant diagnoses included erosions and ulcers (26%; n = 71 ), small bowel (SB) angioectasia (AE) (10%; n = 27 ), SB tumours (3%; n = 7 ), Crohn's disease (3%; n = 7 ), SB bowel strictures (1%; n = 3 ), and SB varices (1%; n = 2 ). On logistic regression, the presence of diabetes (P = 0.02 ) and the use of warfarin (P = 0.049 ) was associated with increased DY. The DY in Group 2 was 38% which was significantly higher than in Group 1 (P = 0.02 ). While SB tumours were equally common in both groups, AE was commoner in Group 2 (P < 0.001 ). Conclusion . A significant proportion of patients <50 years are referred for CE. Although the DY is lower compared to those ≥50 years, significant pathology is found in this age group. CE is advisable in patients <50 years old with recurrent IDA and negative bidirectional endoscopies.